Innatist and Interactionist Learning Approaches of Elementary School Students’ Language Acquisition - Petra Kristi Mulyani (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2019)
Language acquisition starts in childhood. Oral language is the initial language to learn. Within it, lies norms to make language functional. Children start to function the language through communication. Communication provides an identity that shapes them into different settings. As language acquisition is unique and individual, experts have been studying to interpret it. There are at least three theorists of language acquisition. They are a behaviorist, innatist, and interactionist. Experts are debating on which theory provides the most appropriate approaches for the students. The discussion will compare innatist and interactionist approaches to the students’ first and second language acquisition. It describes how the educational program would be like when using innatist and interactionist learning approaches. There are also critiques on innatist and interactionist approaches. A suggestion is provided to strategically integrate both approaches to understand language acquisition process in both first and second language students.